2017
DOI: 10.1016/j.ptsp.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Does kinesiology taping of the ankles affect proprioceptive control in professional football (soccer) players?

Abstract: Objective: To determine whether the bilateral application of kinesiology tape (KT) to professional footballers' ankles can improve their lower limb proprioception.Design: A single blind randomised crossover study. Participants were randomly assigned to complete a proprioception test in either a taped or not taped condition first. Following a wash out period, participants were then re-tested in the alternate condition.Setting: A UK Championship League Football Club, mid-season.Participants: Twenty male professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 30 publications
0
27
1
3
Order By: Relevance
“…When compared to traditional white tapes, KT has demonstrated inconclusive findings, for 56 example, in one study postural stability was shown to be improved following a of localized 57 fatigue protocol (13), whereas another study identified limited tape application benefits in 58 relation to fibularis longus activity during sudden inversion perturbation (9). Furthermore, 59 equivocal findings have been reported regarding range of motion (2, 37), strength (2, 29) 60 proprioception (6,18,21,27) postural stability (15,32) and functional performance (8,32). 61…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…When compared to traditional white tapes, KT has demonstrated inconclusive findings, for 56 example, in one study postural stability was shown to be improved following a of localized 57 fatigue protocol (13), whereas another study identified limited tape application benefits in 58 relation to fibularis longus activity during sudden inversion perturbation (9). Furthermore, 59 equivocal findings have been reported regarding range of motion (2, 37), strength (2, 29) 60 proprioception (6,18,21,27) postural stability (15,32) and functional performance (8,32). 61…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…2 To examine KT as a potential intervention for athletes at risk for ankle trauma, investigators analyzed the COP of professional soccer players when comparing a KT application with a no-tape condition. 4 Though there is no gold standard for measuring ankle proprioception, the investigators utilized a moving target program from the balance module of a Kin-Com ® 125AP isokinetic dynamometer (East Ridge, TN). The participants controlled their COP to track an on-screen visual stimulus to simulate the ankle instability that might occur in a soccer match.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
“…The participants controlled their COP to track an on-screen visual stimulus to simulate the ankle instability that might occur in a soccer match. 4 Researchers observed that an application of KT had no significant effect on the COP of professional soccer players. 4 Although no positive effect was observed following the application of KT, consideration should be given to the population in question, as this finding may not translate to amateur athletes or the general population.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Darunter waren auch die einzigen beiden Studien, welche eine Verblindung durchführten. Bailey und Firth [13] verblindeten den Untersucher und Nunes et al [16] verblindeten sowohl die Probanden als auch den Untersucher. Diese Verblindung wurde in beiden Fällen durch das Überstreifen einer Socke über die kinesiologische Tapeanlage bzw.…”
Section: Besonderheiten Der Studien Ohne Signifikanten Effektunclassified